THERMAL MONITORING OF NORTH PACIFIC VOLCANOES FROM SPACE - Dehn J.; Dean K.; Engle K. (My University, 2000)
Long-term thermal modeling of volcanoes using satellite imagery provides an effective tool for monitoring remote yet dangerous volcanoes in the North Pacific. This region includes volcanoes in Alaska, the Aleutian Islands, and the Kamchatkan Peninsula. Thermal infrared data collected multiple times per day from weather satellites show distinct signatures for three different types of volcanic activity at different volcanic centers. Near real-time automated techniques are being developed to monitor relative changes in radiant temperature at volcanoes in this region. Radiant temperature values as a function of time are extracted and compared to background values for a series of active volcanoes. By establishing a long-term thermal record for these volcanoes, significant deviations indicative of an impending eruption can be detected. This tool is used to search for precursors to explosive eruptions in order to increase warning times and hazard mitigation for these potentially catastrophic events. A six year archive of satellite imagery has been compiled for this active region, and is available for study.